Evaluation of selected health seeking behaviours and prevention of osteoporosis in perimenopausal women - Ewa Rudnicka-Drożak; Krzysztof Jankowski; Paula Jankowska; Monika Majcher; Agnieszka Jankowska (Kazimierz Wielki University, 2019)
Introduction 'Osteoporosis is a metabolic bone disease, a condition characterized by low bone mass and microarchitectural deterioration of bone tissue, leading to enhanced bone fragility and a consequent increase in fracture risk'. It is a contemporary, currently recognized definition of osteoporosis formed by the research group of World Health Organization. It is estimated that due to increased life expectancy, the number of fractures may rise three times within 60 years, principally given the lack of appropriate strategies of osteoporosis prevention. Objective The aim of the paper was to evaluate selected health-seeking behaviours as well as the knowledge of osteoporosis prevention rules in perimenopausal women. Material and methods The research method was a self-made survey questionnaire. The population under the survey involved 450 female patients aged 40-65 selected at random. Results Survey results indicate insufficient knowledge and health-seeking behaviours among the respondents. What is also striking is the fact of underestimating the relationship between the use of stimulants (cigarettes, coffee, alcohol) and osteoporosis, not enough physical activity of the subjects as well as the lack of systematic gynecological control concerned with hormonal balance disorders (characteristic for the perimenopausal period). Conclusions Insufficient knowledge of prevention and proper health-seeking behaviours contribute to the increase in the incidence of osteoporosis.